HOW DO PLANTS GROW AT HOME? (STEAM PROJECT: AUTOMATIC IRRIGATION SYSTEM AND GROWTH GRAPH) (Modern education and development, 2025)
This article aims to guide primary school students in the practical study of plant growth and development processes based on the STEAM (Science, Technology, Engineering, Arts, Mathematics) approach. It details a project involving the creation of an automatic irrigation system using simple household materials and monitoring plant growth dynamics through mathematical graphs. The article emphasizes the importance of integrating theoretical knowledge with practice, developing critical and creative thinking, fostering teamwork, and problem-solving skills. Additionally, project-based teaching methods and their role in enhancing the scientific potential of young children are discussed.